Ἐν Δέραις καλουμέναις τῆς σφετέρας: Αναζητώντας μία αρχαία θέση και ένα ιερό στην βόρεια Μεσσηνία - Κουρσούμης Σωκράτης Σ. (Tekmeria, 2013)
<!–[if gte mso 9]> Normal 0 false false false <![endif]–><span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: Arial; mso-bidi-font-family: ’Times New Roman’; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Pausanias attests to the Messenian Derai as the place in which the first conflict of the Second Messenian War took place, between the Spartan army and the Messenian guerillas of Aristomenes. The site may be located at northern Messenia, in the area of the modern Messenian – Arcadian borderline, near Mount Tetrazi and the sources of the river Neda, to the south of Mount Lykaion. Fragmentary inscriptions from Messene and Olympia record the borderline marking between the regions of Megalopolis and Messene, attesting to one or more than one sites called dera, obviously remote and inaccessible; the same texts record an unknown Artemis sanctuary. Moreover, Strabo attests to an Arcadian sanctuary of Artemis Eleia to the south of Lykaion, while Pausanias refers to a remote Messenian site called Elaios as well as to the Arcadian mountain of Elaion, which both may be identified to the modern Mount Tetrazi. Recent excavations near the modern village of An<span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: Arial; mso-bidi-font-family: ’Times New Roman’; letter-spacing: -.15pt; mso-ansi-language: EL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">ο<span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: Arial; mso-bidi-font-family: ’Times New Roman’; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Melpeia at a remote site called Petroula/ Pisailias, on the southern foothills of Mount Tetrazi brought to light a Doric temple dated to the Archaic – Classical times, which may be identified as the aforementioned sanctuary of Artemis Dereatis/<span style="font-size: 10.0pt; line-height: 115%; font-family: Gentium; mso-fareast-font-family: Arial; mso-bidi-font-family: ’Times New Roman’; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Eleia.<!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>